2015
DOI: 10.1186/s13287-015-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin promotes bone marrow mesenchymal stem cell-based calvarial bone regeneration in mini swine

Abstract: IntroductionStem cells have great therapeutic potential due to their capacity for self-renewal and their potential for differentiating into multiple cell lineages. It has been recently shown that the host immune system has fundamental effects on the fate of transplanted mesenchymal stem cells during bone repair, where the topical administration of aspirin is capable of improving calvarial bone repair in rodents by inhibiting tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) production. This study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 31 publications
3
49
1
Order By: Relevance
“…In addition to its long-term application as an antipyretic and analgesic for postoperative pain relief [21], ASP is also reported to substantially improve immunomodulatory function, manifested as regulatory T cells upregulation and Th17 cells downregulation in vitro [22]. In addition, systemic use of ASP revealed enhanced bone regeneration in vivo [23]. Moreover, some scholars have recently demonstrated that low doses of ASP can regulate the balance between bone resorption and bone formation in osteoporosis caused by ovariectomy [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its long-term application as an antipyretic and analgesic for postoperative pain relief [21], ASP is also reported to substantially improve immunomodulatory function, manifested as regulatory T cells upregulation and Th17 cells downregulation in vitro [22]. In addition, systemic use of ASP revealed enhanced bone regeneration in vivo [23]. Moreover, some scholars have recently demonstrated that low doses of ASP can regulate the balance between bone resorption and bone formation in osteoporosis caused by ovariectomy [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, a low dose of aspirin can promote BMSCs' proliferation. 44 The ACS-CCM prepared in this study showed satisfactory cytocompatibility and could promote the adhesion and proliferation of BMSCs ( Figure 5). In addition, the number of cells on the 50 mg ACS-CCM samples was considerably higher than that on the other membranes.…”
mentioning
confidence: 73%
“…There are only a few reports on the effects of ASA on stem cell differentiation. With its inhibiting effect on tumor necrosis factor‐α (TNF‐α) and interferon‐γ (IFN‐γ) production, aspirin has been shown to promote the osteogenesis of bone MSC in vitro, improve calvarial bone repair in vivo (Cao et al, ), and limit ectopic bone formation caused by BMP‐2 treatment (Subramanian et al, ). While there are contradicting results on the effect of ASA on cell proliferation, there are reports showing that aspirin can enhance osteogenic and cardiomyocyte differentiation of bone marrow‐derived MSC (Hao, Shi, Zhou, Wang, & Nie, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports on the effects of ASA on stem cell differentiation. With its inhibiting effect on tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) production, aspirin has been shown to promote the osteogenesis of bone MSC in vitro, improve calvarial bone repair in vivo (Cao et al, 2015), and limit ectopic bone formation caused by BMP-2 treatment (Subramanian et al, 2015). (Alcaraz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%